Kelayakan media e-encyclopedia pada submateri kingdom plantae hasil inventarisasi tumbuhan obat pasca melahirkan suku Melayu Desa Bentunai - Rosanti, Melsinta; Panjaitan, Ruqiah Ganda Putri; Wahyuni, Eko Sri; Wardhani, Hilda Aqua Kusuma (Biosfer: Jurnal Pendidikan Biologi, 2024)
Learning media can help clarify the meaning of the message to be conveyed so that learning objectives can be achieved. Learning media can be presented in non-print or electronic form and can be developed from the results of research such as an inventory of medicinal plants. This research aims to determine the feasibility of e-encyclopedia media as a result of postnatal medicinal plant inventory of the Malay tribe of Bentunai Village. This research uses the R&D (Reseach & Development) research method, but it is only carried out until the design revision stage. The media feasibility test was carried out by validation by five validators and analyzed using Aiken V validity and ICC (Intraclass Correlation Coefficient) reliability. The aspects assessed are content, writing, convenience and appearance. The results of the e-encyclopedia validator analysis showed that the Aiken validity value in the content aspect in the very high category, the writing aspect in the very high category, the convenience aspect in the very high category and the appearance aspect was in the very high category. The average validity of these four aspects is in the very high category. The results of the ICC reliability analysis show a reliability and agreement between validators is at a good criteria index. So, it can be concluded that the e-encyclopedia developed as a result of the inventory of postnatal medicinal plants from the Malay tribe of Bentunai Village is suitable for use as a learning medium.